Service Quality Analysis to Increase Customer Satisfaction at Hypermart - Darma, Vincent Setya; Jesika Suryani; Filbert Hwang; William Phang (Journal of Current Research In Multidisciplinary, 2023)
This research aims to analyze whether service quality can increase customer satisfaction. Collecting data from distributed questionnaires. When the data has been collected, it is converted to Excel so that it can be processed. Then the data will be divided into 2, where the first data is importance and the second data is performance. From the various analyses that have been carried out, it can be concluded that there is only one indicator that shows a positive value. The Q4 indicator occupies the first position, showing a gap value of -0.43, and the Q2 indicator occupies the last position, showing a gap value of 0.1. Then the quadrant results show that Q4 and Q6 must be prioritized to improve their performance because they have a high level of importance. Q8, Q5, and Q1 continued their performance because they had good performance and a high level of importance for Ritel. Q7 and Q3 should not be given too much priority because they have a low level of importance and low performance too. Q10 and Q2 have excessive performance compared to their importance; therefore, it is better not to prioritize them too much.